Digital Marketing Strategy to Enhance Competitive Advantage in Offline Mobile Phone Retail Stores in the Greater Jakarta (Jabodetabek) Area: A Systematic Literature Review - Muphimin Muphimin; Arissetyanto Nugroho; Zulkifli Zulkifli (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Offline mobile phone retail stores in the Greater Jakarta (Jabodetabek) area face increasing competitive pressure due to the growth of e-commerce, shifts in consumer behavior, and the rising adoption of digital marketing and digital payment systems. Meanwhile, the growth of the national smartphone market has not been fully accompanied by improved performance of physical retail outlets. This condition indicates a gap between industry growth and the competitiveness of offline stores, highlighting the need for a strategic model that integrates operational capabilities with digital marketing practices. This study aims to develop a conceptual model explaining the roles of supply chain management, service quality, customer experience, and digital payment in influencing competitive advantage, with digital marketing as a mediating variable and strategic flexibility as a moderating variable. The research employs a qualitative approach using a Systematic Literature Review (SLR) design, following stages that include formulating research questions, establishing inclusion–exclusion criteria, searching scientific databases, selecting relevant articles, extracting data, and conducting thematic analysis to synthesize prior research findings. The review results indicate that operational capabilities and service quality contribute to competitiveness, digital marketing strengthens value perception and purchase decisions, and strategic flexibility enhances the effectiveness of strategies in responding to market dynamics. However, prior studies generally examine these relationships partially and do not integrate them into a comprehensive model. In conclusion, the integration of operational and digital marketing factors through mediation–moderation mechanisms is necessary to enhance the adaptive and sustainable competitive advantage of offline mobile phone retail stores.